Gas Transport in Porous Media - Ho, Clifford K.; Ho, Clifford K.; Webb, Stephen W.; Webb, Stephen W. (Theory and Applications of Transport in Porous Media, 2006)
This book presents a compilation of state-of-the art studies on gas and vapor transport processes in porous and fractured media. A broad set of models and processes is presented, including advection/diffusion, the Dusty Gas Model, enhanced vapor diffusion, phase change, coupled processes, solid/vapor sorption, and vapor-pressure lowering. Numerous applications are also presented that illustrate these processes and models in current problems facing the scientific community. This book fills a gap in the general area of transport in porous and fractured media - an area that has historically been dominated by studies of liquid-phase flow and transport. This book identifies gas and vapor transport processes that may be important or dominant in various applications, and it exploits recent advances in computational modeling and experimental methods to present studies that distinguish the relative importance of various mechanisms of transport in complex media. Audience: This book offers essential reading to researchers and graduate students in soil science, hydrology, as well as civil engineering, and mechanical engineering. Also employees at government institutions, national laboratories, practicing environmental engineers and engineering consultants can find valuable information in this book. Finally it can serve as a textbook to students with a basic background in thermodynamics and fluid mechanics.